Emission Control by Molecular Manipulation of Double‐Paddled Binuclear PtII Complexes at the Air‐Water Interface. Issue 3 (10th January 2020) - Adachi, Junya; Mori, Taizo; Inoue, Ryo; Naito, Masaya; Le, Ngoc Ha‐Thu; Kawamorita, Soichiro; Hill, Jonathan P.; Naota, Takeshi; Ariga, Katsuhiko
Abstract: Molecular functions depend on conformations and motions of the corresponding molecular species. An air–water interface is a suitable asymmetric field for the control of molecular conformations and motions under a small applied force. In this work, double‐paddled binuclear Pt II complexes containing pyrazole rings linked by alkyl spacers were synthesized and their orientations and emission properties dynamically manipulated at the air–water interface. The complexes emerge from water with concurrent variation of interface orientation of the planes of the Pt II complexes from perpendicular to parallel during mechanical compression suggesting a unique 'submarine emission'. Phosphorescence of the complexes is quenched at the air–water interface prior to monolayer formation with intensities subsequently rapidly increasing during monolayer compression. These results indicate that asymmetric reactions and motions might be controlled by applying mechanical force at the air–water interface. Abstract : The orientations and emission properties of double‐paddled binuclear Pt II complexes were dynamically manipulated at the air–water interface. The phosphorescence of the complexes is quenched at the air–water interface prior to monolayer formation with intensities subsequently rapidly increasing (similarly to aggregation‐induced emission) during monolayer compression.